A Thermal Comfort Investigation of a Facility Department of a Hospital in Hot-Humid Climate: Correlation between Objective and Subjective Measurements. Issue 5 (October 2013) - Azizpour, F.; Moghimi, S.; Lim, C. H.; Mat, S.; Salleh, E.; Sopian, K.
A field study on assessing thermal comfort has been performed on one of the large-scale hospitals in Malaysia, a country where the climate is classified as hot-humid. The main objective of this study was to examine the comfort criteria by American Society of Heating, Air conditioning & Refrigeration Engineers, US (ASHRAE) standards in hot-humid regions and also to find the correlation between predicted mean vote (PMV) according to Fanger's theory and thermal sensation vote (TSV) according to occupant votes. Therefore, both objective and subjective data was collected in this hospital, and this study's results have confirmed that the preferred temperature is not necessarily in compliance with a neutral temperature, and people in hot-humid areas would prefer cooler environment to neutral temperature. In addition, by analyzing linear regression, a strong correlation between PMV and TSV was found while R 2  = 0.950, and also the neutral temperature point in this field study was around +0.75 on the seven-point ASHRAE thermal sensation scale.